2014
DOI: 10.1007/s12192-013-0468-1
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Hsp72 concentration relates to a minimum endogenous criteria during acute exercise-heat exposure

Abstract: Extracellular heat shock protein 72 (eHsp72) concentration increases during exercise-heat stress when conditions elicit physiological strain. Differences in severity of environmental and exercise stimuli have elicited varied response to stress. The present study aimed to quantify the extent of increased eHsp72 with increased exogenous heat stress, and determine related endogenous markers of strain in an exercise-heat model. Ten males cycled for 90 min at 50 % V : O 2peak in three conditions (TEMP, 20°C/63 % RH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
68
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(80 citation statements)
references
References 76 publications
9
68
3
Order By: Relevance
“…Biochemical methods to detect protein concentrations with a sensitivity of down to 1 ng•mL −1 would therefore not be able to detect the true resting concentration or indeed any small increase from resting. This may partly explain why Gibson et al (2014) only detected HSP70 changes when T core changes were in excess of 2 ºC. However, it is important to note that the extent of the HSP change in the current study (16%) is a very modest increase when compared to existing studies investigating lower body exercise, where increases of 200-1600% have been documented (Yamada et al, 2008).…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…Biochemical methods to detect protein concentrations with a sensitivity of down to 1 ng•mL −1 would therefore not be able to detect the true resting concentration or indeed any small increase from resting. This may partly explain why Gibson et al (2014) only detected HSP70 changes when T core changes were in excess of 2 ºC. However, it is important to note that the extent of the HSP change in the current study (16%) is a very modest increase when compared to existing studies investigating lower body exercise, where increases of 200-1600% have been documented (Yamada et al, 2008).…”
Section: Discussioncontrasting
confidence: 52%
“…Given the importance of temperature elevations in this response (Welc et al, 2012), this exercise modality may particularly benefit from interventions increasing heat stress, because in contrast to lower body exercise, upper body exercise generates less metabolic heat and as such the increases in T core for the same relative exercise intensity are lower for this modality (Gass & Gass, 1998). Lower body exercise comparable in relative intensity and duration as the present study induces two to three times the increase in T core when performed in cool or thermo-neutral conditions (Gibson et al, 2014;Niess et al, 2003;. Previous studies support the hypothesis that exercise that results in a higher T core magnifies the IL-6 response when compared to a CON condition.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…iHSP70 levels increase in response to exercise-induced stressors such as heat, reactive oxygen species (ROS), and hypoxia in cells (Fehrenbach and Northoff 2001). Actually, a single bout of exercise increases circulating eHSP70 level (Walsh et al 2001;Febbraio et al 2002;Fehrenbach et al 2005) and heat stress further boosts this increase (Gibson et al 2014). However, Fortes and Whitham (2011) reported that eHSP70 in the saliva unchanged during and until 20 min after the exercise (60 min of treadmill running at 50−70 % VO 2max ) with hot environment (30°C).…”
Section: Introductionmentioning
confidence: 99%
“…Increased extracellular heat shock protein 72 (eHsp72) concentrations are evident in response 61 to exercise with the greater increases 62 during exercise-heat stress predicted by the magnitude of change in rectal temperature 63 (Gibson et al, 2014) and exercise intensity (Periard, Ruell, Caillaud, & Thompson, 2012). 64…”
Section: Introduction 60mentioning
confidence: 99%